1998
DOI: 10.1080/001401398187260
|View full text |Cite
|
Sign up to set email alerts
|

Predictive models of carpal tunnel syndrome causation among VDT operators

Abstract: Carpal tunnel syndrome (CTS), a cumulative trauma disorder of the hand and wrist, is one of the most common disabling injuries experienced by video-display terminal (VDT) operators. The purpose of this study was to develop a theoretically based operational quantitative predictive model of the risk of work-related CTS among VDT operators. A total of 100 female VDT operators, who performed a variety of office functions, were studied at a major midwestern university. Data were collected on job exposure, anthropom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 3 publications
2
40
0
3
Order By: Relevance
“…Visible symptoms occur in 50-90 percent of computer workers [51,54]. The prevalence and severity of symptoms are significantly correlated with the amount of period spent performing computer jobs [53].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visible symptoms occur in 50-90 percent of computer workers [51,54]. The prevalence and severity of symptoms are significantly correlated with the amount of period spent performing computer jobs [53].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, symptoms in the neck, shoulder blades, back, and eyes are more prevalent. Matias, Salvendy and Kuczek [53] referred to an 8-38 percent incidence and predicted a 40 percent probability of hand injuries in computer employees. Nainzadeh, Malantic-Lin, Alvarez and Loeser [52] reported an 80 percent prevalence of tension neck syndrome in computer (office) workers.…”
Section: Resultsmentioning
confidence: 99%
“…Further, good forearm support has been shown to reduce the musculoskeletal exposure, and discomfort in VDU work [13][14][15][16] Dainoff et al [7] reported about an ergonomic intervention, which included also a use of motorized adjustable workstations in VDU work, that musculoskeletal pain among the VDU workers reduced significantly. According to Schofield et al [17] standing and typing produced an average of 13% higher energy expenditure than sitting and typing did, and it can therefore reduce the risk of weight gain.…”
Section: Introductionmentioning
confidence: 99%
“…Sit-stand workstations offer one possibility of decreasing sedentary behavior and varying work postures during work day [6][7][8][9]. Workers can select low-sitting, high-sitting, and standing postures according to their needs and tasks and adjust the work station height easily [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining or increasing grip strength may be effective for preventing wrist injuries in computer users. Matias et al (1998) reported that the incidence of wrist injuries is 8 to 38% and the probability of injury is 40% among computer workers. Rasotto et al (2015) reported an improvement on upper limb pain and neck disability with concomitant increases in grip strength.…”
Section: Discussionmentioning
confidence: 99%